2020
DOI: 10.1029/2020gl088803
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Dynamo Electrodynamics With Spiral Currents Driven by Strong Winds Revealed by Vapor Trails and Sounding Rocket Probes

Abstract: We investigate the forces and atmosphere‐ionosphere coupling that create atmospheric dynamo currents using two rockets launched nearly simultaneously on 4 July 2013 from Wallops Island (USA), during daytime Sq conditions with ΔH of −30 nT. One rocket released a vapor trail observed from an airplane which showed peak velocities of >160 m/s near 108 km and turbulence coincident with strong unstable shear. Electric and magnetic fields and plasma density were measured on a second rocket. The current density peaked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Sounding rockets have sometimes provided simultaneous measurements of plasma densities and neutral winds suitable for testing the wind shear theory. Some studies found Es layers near the height of a strong negative shear of the eastward wind, supportive of the wind shear theory (e.g., Bishop et al, 2005;Larsen et al, 1998;Pfaff et al, 2020). However, Hall et al (1971) observed an Es layer with a positive shear, contrary to the wind shear theory.…”
mentioning
confidence: 89%
“…Sounding rockets have sometimes provided simultaneous measurements of plasma densities and neutral winds suitable for testing the wind shear theory. Some studies found Es layers near the height of a strong negative shear of the eastward wind, supportive of the wind shear theory (e.g., Bishop et al, 2005;Larsen et al, 1998;Pfaff et al, 2020). However, Hall et al (1971) observed an Es layer with a positive shear, contrary to the wind shear theory.…”
mentioning
confidence: 89%
“…The weak ozone hole was caused by abnormally strong planetary wave activity originating in the subtropical Pacific Ocean east of Australia and over the eastern South Pacific [ 19 , 21 , 22 ]. These waves weakened the stratospheric polar vortex, which led to a warming of the polar stratosphere, starting in mid-August [ 23 ]. The resulting above-normal temperature in the lower stratosphere reduced the occurrence of polar stratospheric clouds (PSCs), which provide surfaces for heterogeneous chemical reactions involving chlorine that destroy ozone catalytically.…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionsmentioning
confidence: 99%
“…The unusual warming of the Antarctic stratosphere in September 2019 (Sect. 2.3 ) may have exacerbated the extremely dry conditions observed during the summer of 2019/20 in the Southern Hemisphere [ 23 , 40 – 44 ], leading to devastating wildfires in Australia [ 45 ]. Specifically, the stratospheric warming event influenced the troposphere from mid-October 2019 by forcing the SAM from a positive phase to a negative phase, which enhanced anomalously hot and dry conditions in eastern Australia [ 44 ].…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionsmentioning
confidence: 99%
“…Earlier studies based on various observations and modeling techniques, particularly those pertaining to empirical curve fitting of Sq current variation have been conducted (e.g., S. S. Chen et al, 2020Chen et al, , 2021Vanhamäki et al, 2020;Yamazaki et al, 2009Yamazaki et al, , 2010Yamazaki et al, , 2011. These studies explored the dynamics of the ionosphere and its interaction with the magnetosphere, in particular, examining the consequences of universal time (UT), season and day-to-day variations (e.g., S. S. Chen et al, 2021;Kirchhoff & Carpenter, 1976;Pfaff et al, 2020;Schlapp & Butcher, 1995;Yamazaki et al, 2016), including the effects of local neutral winds (e.g., Maute, 2017;Yamazaki et al, 2021). It was remarked that due to variations in the ionospheric conductivity and neutral winds, the Sq current system exhibits hemispheric asymmetry, with its strength in the summer hemisphere being greater than that in the winter hemisphere.…”
mentioning
confidence: 99%